Problems of Criminal Applications Law in the Life of Indonesian Communities and Cultures - Rina Rohayu Harun; Bahri Yamin; Mualimin Mochammad Sahid (Magister of Law, Faculty of Law, Universitas Mataram, 2024)
Indexed by Scopus